Numerical Treatment of a Two-Dimensional Vertically-Averaged Groundwater Flow Model Using Alternating Direction Explicit Methods - Supawan Yena; Nopparat Pochai (My University, 2020)
Leachate from a landfill can flow down and contaminate groundwater.Mathematical models are often used to describe groundwater flow, which can help designers to identify an appropriate location for a landfill area.We focused on simulation of hydraulic head of groundwater under landfill construction in a rural area.We used a partial differential equation model called two-dimensional vertically-averaged groundwater flow model to explain groundwater volume, in particular, to explain the hydraulic head of the groundwater which strongly affected the groundwater quality.We applied two alternating direction explicit methods to the groundwater flow model under general boundary conditions and rates of change of boundary conditions to obtain an approximate hydraulic head of groundwater.An alternating direction explicit method for all types of boundaries is used to find approximate solutions.The traditional alternative direction explicit method was modified to form our modified alternative direction explicit method.The results of all method are closed.The traditional alternative direction explicit method and the modified alternative direction explicit method led to more accurate solutions than forward time centered space in heterogeneous aquifer, two methods ensured that a stable solution of all interior points can be obtained by using a fine grid spacing.
Keywords: Groundwater flow and contamination studies